Evidence for two gene pools of the lima bean, Phaseolus lunatus L. in the Americas - Gutiérrez Salgado, A.; Gepts, Paul L.; Debouck, Daniel G. (Springer, 1995)
The lima bean, Phaseolus lunatus L., is a bean species with a broad distribution in the Americas that rivals that of common bean (P. vulgaris). In order to better understand the organization of genetic diversity and the pattern of domestication in lima bean, a review was conducted of the available information on the geographic distribution of wild and cultivated forms of this species. In addition, one-dimensional SDS polyacrylamide gel electrophoresis of seed proteins was also conducted on a sample of 84 wild, 6 weedy, and 426 cultivated forms. Results show that wild forms can be divided into two groups, one with smaller seeds and a very extensive distribution that includes Mexico, Central America, and the eastern slope of the Andes, and the other with a more circumscribed distribution on the western slope of the Andes in Ecuador and northern Peru. Electrophoretic analyses of seed proteins confirmed this subdivision and, additionally, showed that the large-seeded cultivars had been domesticated from the large-seeded wild lima beans in western South America. For the small-seeded lima bean cultivars, it was not possible to determine a domestication center as the most abundant protein pattern in the cultivars also had a widespread distribution in the small-seeded wild progenitor. Electrophoretic analyses showed, however, that domestication led to a reduction of genetic diversity in the small-seeded, Mesoamerican group, but not in the large-seeded group. The latter may be due to insufficient sampling of the larger-seeded, wild germplasm